Wintertime black carbon assessment in dhaka, Bangladesh: Integrated health risk analysis - A.K.M. Nayem; Shahid Uz Zaman; Farida Begum; Abdus Salam (Heliyon)
This study investigated the ramifications of black carbon (BC) emissions on human health during the winter season of December 2019 to February 2020 in Dhaka, Bangladesh. BC, arising from incomplete combustion of fossil and biofuels, underwent meticulous measurement of densities, concentrations, and emissions at two pivotal sites. Employing low-volume air samplers with Quartz filters and subsequent analysis with an Aethalometer (Soot scanner, OT21, USA), the study unveiled monthly average BC densities of 1.64 μg cm−2, concentrations of 4.99 μg m−3, and emissions of 0.038 μg J−1. Health risk assessments revealed higher cancer risks (CRs) at Site-1 (children: 2.82 × 10−4 and adult: 4.72 × 10−4) compared to Site-2 (children: 2.56 × 10−4 and adult: 4.30 × 10−4). Hazard quotients (HQs) averaged 0.29 for children and 0.19 for adults in Dhaka. BC exposure escalated relative risks (RR) for all-cause mortality (RR = 1.136), cardiovascular mortality (RR = 1.169), and respiratory mortality (RR = 1.277). These findings underscore the substantial implications of BC's influence, particularly in a nation like Bangladesh, and furnish invaluable insights into aerosol characteristics and emission sources in South Asia, facilitating the formulation of emission inventories.